SUBJEKTIVITAS DALAM PENAFSIRAN AL-QURAN: FENOMENA TAFSIR BERCORAK SEKTARIAN - Mawardi, Mawardi (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2018)
Tafseer was issued from the desire of mufaseer in revealing the content of Qur'an which aims to answer various problems of life. In this effort, some commentators forced the Qur'an to legitimize opinions and groups. In order for its purpose to be achieved, the mufaseer interpretate (ta?wil) the verses in order to fit the groups and schools followed.